Maine : a novel - Sullivan, J. Courtney (New York : Alfred A. Knopf, 2011)
Three generations of women converge on the family beach house in this story of love and dysfunction.
"This is a Borzoi book"--T.p. verso.
Keywords: Women -- Family relationships -- Fiction; Family secrets -- Fiction; Maine -- Fiction; Domestic fiction; Humorous fiction